2022
DOI: 10.1136/bmjopen-2022-061870
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen for treatment of long COVID-19 syndrome (HOT-LoCO): protocol for a randomised, placebo-controlled, double-blind, phase II clinical trial

Abstract: IntroductionLong COVID-19, where symptoms persist 12 weeks after the initial SARS-CoV-2-infection, is a substantial problem for individuals and society in the surge of the pandemic. Common symptoms are fatigue, postexertional malaise and cognitive dysfunction. There is currently no effective treatment and the underlying mechanisms are unknown, although several hypotheses exist, with chronic inflammation as a common denominator. In prospective studies, hyperbaric oxygen therapy (HBOT) has been suggested to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In 2022, Kjellberg et al [27] reported a protocol for a phase II, randomized, placebocontrolled, double-blind clinical trial. This study aimed to explore the potential of HBOT in enhancing the health-related quality of life (HRQoL) in long COVID patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Kjellberg et al [27] reported a protocol for a phase II, randomized, placebocontrolled, double-blind clinical trial. This study aimed to explore the potential of HBOT in enhancing the health-related quality of life (HRQoL) in long COVID patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study was small and had no control group. A small ( n =73) randomised, placebo-controlled, double-blind trial has also shown benefits of daily HBOT [ 115 ] and a phase II clinical trial is in progress [ 116 ]. During HBOT, the arterial O 2 tension typically exceeds 1500 mmHg, and levels of 200–400 mmHg occur in tissues [ 117 ], consistent with it having an impact on endometrial tissue oxygen levels.…”
Section: Covid-19 and Potential Aub-imentioning
confidence: 99%
“…One patient has been reported under treatment with enhanced external counterpulsation ( 100 ). Cognitive behavioral therapy ( 101 , 102 ), breath retraining, and paced postural exercises incorporating breathing, such as yoga and hyperbaric oxygen, have been proposed ( 103 105 ). The increased demand for autonomic specialists and clinics since the start of the COVID-19 pandemic reveals the need for more resources to adequately care for this patient population ( 106 ).…”
Section: Treatmentmentioning
confidence: 99%